Visual Emotive Meaning in Conservation Advocacy: An Analysis of WWF’s Public Service Announcements - Xu Song; Kesumawati A. Bakar (SAGE Open)
World Wildlife Fund (WWF) has developed a diverse range of emotionally-charged print Public Service Announcements (PSAs) to draw the public’s attention to wildlife conservation. These PSAs contain images of powerful visual effects, which can resonate with people’s emotions, and thereafter influence their behaviors. This research seeks to unveil how emotions are delivered by these PSAs. To achieve this aim, 144 multimodal print WWF PSAs on wildlife conservation were selected as the corpus. The visuals are prominent in each PSA, with English serving as the accompanying language. The visual emotive meaning of these PSAs was examined by using Martin and Rose’s appraisal system combined with Painter et al.’s theory. The findings revealed that WWF’s persuasive strategies predominantly revolve around evoking negative emotions through negative attitudes, unmediated perspectives, enlarged graduations, and activated ambiance in the PSAs. The use of contrast and metaphor was also revealed to be powerful tools for enhancing emotion. In general, this research expanded the application of appraisal theory to the interpretation of the emotive meaning of images. Meanwhile, by uncovering the emotive meaning of WWF print PSAs, it also contributes to the study of PSAs. Additionally, the framework of analyzing the emotive meaning of visual images in this research can also be applied to assess visual emotions in other types of advertising, textbook illustrations, cartoons, the visual scenes in videos, as well as conservationists’ visual design.